Rancang Bangun Sistem Informasi Keuangan pada Koperasi Pengayoman Intan Lapas Garut Berbasis Web - Asep Deddy Supriatna; Yosep Septiana; Teguh Aji Renaldi (Institut Teknologi Garut, 2022)
The Pengayoman Diamond Cooperative (KOPIN) Garut Prison was formed in 1984 with the aim of building, developing the potential and increasing the economic capacity of members based on the principle of kinship of members and for the welfare of members. In managing the work process of the Garut Correctional Cooperative (KOPIN) Garut prison consists of management of savings and loans, management of the trade sector, management of the livestock sector and management of the fishing sector. Based on the results of the analysis, it can be concluded that the manual management system has created several obstacles, including low data accuracy and low response time, thereby reducing service to its members. As an alternative solution is the development of a web-based system with the methodology used is the Rational Unified Process (RUP). The results of this study indicate that the application system built is relevant to the expected goals in accordance with the alpha testing that was carried out. Thus it can be concluded that with the aim of developing this system, it has been able to improve services to members.